2005
DOI: 10.1534/genetics.104.035048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Chromosomal Distribution of Galileo, Kepler and Newton, Three Foldback Transposable Elements of the Drosophila buzzatii Species ComplexSequence data from this article have been deposited in the EMBL/GenBank Data Libraries under accession nos. AY756161, AY756162, AY756163, AY756164, AY756165, AY756166, AY756167, AY756168, AY756169, AY756170.

Abstract: Galileo is a foldback transposable element that has been implicated in the generation of two polymorphic chromosomal inversions in Drosophila buzzatii. Analysis of the inversion breakpoints led to the discovery of two additional elements, called Kepler and Newton, sharing sequence and structural similarities with Galileo. Here, we describe in detail the molecular structure of these three elements, on the basis of the 13 copies found at the inversion breakpoints plus 10 additional copies isolated during this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 80 publications
2
58
0
Order By: Relevance
“…2B). While other mechanisms may well exist, we note that previous studies indicate that transposable elements similar to Foldback (FB) elements in D. melanogaster (Chia et al 1985;Lovering et al 1991;Casals et al 2003Casals et al , 2005 are capable of mediating such movement.…”
Section: Resultsmentioning
confidence: 70%
“…2B). While other mechanisms may well exist, we note that previous studies indicate that transposable elements similar to Foldback (FB) elements in D. melanogaster (Chia et al 1985;Lovering et al 1991;Casals et al 2003Casals et al , 2005 are capable of mediating such movement.…”
Section: Resultsmentioning
confidence: 70%
“…Some may be for technical reasons (for example, breakage of single fibers), but we also investigated possible interspersion with a major transposon family. The foldback element Galileo was found to accumulate in the heterochromatic regions of several chromosomes and was more pronounced in the microchromosomes of several species from the buzzatii cluster (Casals et al, 2005). However, PCR experiments (data not shown) using single Galileo primers (G7 and E14 in Casals et al, 2005) and a combination of Galileo and pBuM or DBC-150 primers showed little evidence of interspersion between Galileo and pBuM or DBC-150 arrays in genomic regions spanning 0.1-2 kb.…”
Section: Organization Of Pbum and Dbc-150 Repeatsmentioning
confidence: 91%
“…In D. melanogaster, the analysis of thousands of normal flies conducted by Bridges (1935) revealed that the microchromosomes do not undergo crossing-over during meiosis under natural conditions (reviewed by Riddle and Elgin, 2006). Recent studies suggested that suppressed meiotic recombination is probably a characteristic of the microchromosomes found in the buzzatii cluster too (Casals et al, 2005;Kuhn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other TEs, such as P, Hobo, or FB are known to induce chromosomal rearrangements in experimental populations of D. melanogaster (20), but there is no direct evidence of their implication in Drosophila chromosomal evolution. Galileo, together with two closely related elements, Kepler and Newton, were classified as Foldback-like elements because of their long, internally repetitive TIRs (18,21). All copies of Galileo, Kepler, and Newton isolated so far from the genome of D. buzzatii lack any significant protein-coding capacity except for two Galileo copies bearing a short segment with weak similarity to the TPase of element 1360 (Hoppel) (21).…”
mentioning
confidence: 99%
“…Galileo, together with two closely related elements, Kepler and Newton, were classified as Foldback-like elements because of their long, internally repetitive TIRs (18,21). All copies of Galileo, Kepler, and Newton isolated so far from the genome of D. buzzatii lack any significant protein-coding capacity except for two Galileo copies bearing a short segment with weak similarity to the TPase of element 1360 (Hoppel) (21). An experimental search for Galileo sequences in other Drosophila species suggested that this TE has a rather restricted distribution, being only present in the closest relatives of D. buzzatii but not in more distantly related species within the repleta group (21).…”
mentioning
confidence: 99%